2005
DOI: 10.1016/j.atherosclerosis.2005.01.004
|View full text |Cite
|
Sign up to set email alerts
|

High cumulative insulin exposure: a risk factor of atherosclerosis in type 1 diabetes?

Abstract: Background: Since insulin therapy might have an atherogenic effect, we studied the relationship between cumulative insulin dose and atherosclerosis in type 1 diabetes. We have focused on patients with type 1 diabetes instead of type 2 diabetes to minimise the effect of insulin resistance as a potential confounder. Methods: An observational study was performed in 215 subjects with type 1 diabetes treated with multiple insulin injection therapy. Atherosclerosis was assessed by measurement of carotid intima-media… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
1
2

Year Published

2006
2006
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 58 publications
0
20
1
2
Order By: Relevance
“…Despite the fact that our study was not sufficiently powered to detect the diabetes-related differences in IMT which have been reported by Jarvisalo (7), we observed a thicker carotid intima media in the children receiving higher insulin doses (corrected for weight) as also observed in a survey of adult type 1 diabetic patients (15). Both these factors were negatively related to FMD.…”
Section: Endothelium and Sod In Diabetic Childrencontrasting
confidence: 46%
“…Despite the fact that our study was not sufficiently powered to detect the diabetes-related differences in IMT which have been reported by Jarvisalo (7), we observed a thicker carotid intima media in the children receiving higher insulin doses (corrected for weight) as also observed in a survey of adult type 1 diabetic patients (15). Both these factors were negatively related to FMD.…”
Section: Endothelium and Sod In Diabetic Childrencontrasting
confidence: 46%
“…Thus, the significant associations observed in the age-and sex-adjusted models were no longer statistically significant after the adjustment for several confounders and the propensity score. Although some studies showed positive associations between the use of exogenous insulin and the development of CVD, findings from randomized controlled clinical trials showed that the benefits of tight glycemic control in reducing the risk of long-term complications of diabetes (i.e., retinopathy, nephropathy, and neuropathy) outweigh the possible harmful effects of exogenous insulin treatment (13,23). The University Group Diabetes Program showed no evidence that insulin treatment influenced the risk of CVD or mortality (24) in individuals with type 2 diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…The rationale has been based on results from clinical and experimental studies that demonstrated the influence of exogenous insulin on arterial wall changes that ultimately contributed to the development of atherosclerosis (11)(12)(13). However, increased levels of endogenous insulin and the use of exogenous insulin have been associated with increased cardiovascular morbidity and mortality in some studies (3,5-7,9) but not in others (2, 14,15).…”
mentioning
confidence: 99%
“…We calculated the drug-specific daily doses as drug strength and a multiple of pills per day (PPD) which is a function of metric quantity. For those drugs (2) that were missing metric quantity, we assessed the vendor supplied cost-derived imputations from the prescription claims. The estimated values of metric quantity were not equivalent with either clinically-derived values or datadriven estimates for metric quantity.…”
Section: Assessment Of Exposure-response Relationships Using a Time-vmentioning
confidence: 99%
“…Advancing age, comorbid conditions, and cumulative drug exposures contribute to long-term health outcomes among persons with chronic diseases [1][2][3]. Historically, observational studies using administrative pharmacy claims characterize drug exposure as either dichotomized variables or as cumulative CrossMark ← Click for updates doi: 10.7243/2054-9911-3-2 exposure for drug class, combination regimens, or specific drugs [4].…”
Section: Introductionmentioning
confidence: 99%